Scientific system of V.M. Bekhterev: from psychoneurology to biopsychosocial and humanistic paradigms in medicine and psychology - M. A. Akimenko; L. I. Wasserman; E. A. Dubinina; O. Yu. Schelkova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The authors argue historical and conceptual continuity of psychoneurology, of the complex and biopsychosocial approaches to human research, as well as humanistic paradigm in medicine and psychology. It is demonstrated that the principles of the complex approach to human research, which were advanced by V.M. Bekhterev, then were developed and implemented not only at the Psychoneurological Institute, but also in scientific and pedagogical schools of the Leningrad (St. Petersburg) State University. At the current stage of research these principles are largely correspond with the key points of the biopsychosocial approach, which suggests the exploration of complex interrelationships between biological, psychological and social components of a unique human personality in the situation of health and disease.